Evidence for poplar PtaPLATZ18 in the regulation of plant growth and vascular tissues development - Claire Guérin; Marc Behr; Julie Sait; Adeline Mol; Mondher El Jaziri; Marie Baucher (Frontiers in Plant Science, 2023)
IntroductionPlant A/T-rich protein and zinc-binding protein (PLATZ) are plant-specific transcription factors playing a role in plant development and stress response. To assess the role of PLATZs in vascular system development and wood formation in poplar, a functional study for PtaPLATZ18, whose expression was associated with the xylem, was carried out. MethodsPoplar dominant repressor lines for PtaPLATZ18 were produced by overexpressing a PtaPLATZ18-SRDX fusion. The phenotype of three independent transgenic lines was evaluated at morphological, biochemical, and molecular levels and compared to the wild type.ResultsThe PtaPLATZ18-SRDX lines showed increased plant height resulting from higher internode length. Besides, a higher secondary xylem thickness was also evidenced in these dominant repression lines as compared to the wild type suggesting an activation of cambial activity. A higher amount of lignin was evidenced within wood tissue as compared to the wild type, indicating an alteration in cell wall composition within xylem cell types. This latter phenotype was linked to an increased expression of genes involved in lignin biosynthesis and polymerization. DiscussionThe phenotype observed in the PtaPLATZ18-SRDX lines argues that this transcription factor targets key regulators of plant growth and vascular tissues development.